A granitic inclusion suite within igneous zircons from a 3.81 Ga tonalite (W. Greenland): Restrictions for Hadean crustal evolution studies using detrital zircons - Nutman, Allen P; Hiess, Joe (Chemical Geology)
This paper presents an electron microprobe study of inclusions within igneous zircons from ca. 3800 Ma metatonalite sample G97/18. Crystalline inclusions are K-feldspar, plagioclase, quartz, hornblende, biotite, ilmenite and apatite. Additionally, one gl